(untitled) (Global Journal of Science Frontier Research, 2012)
In this work Homotopy Analysis Method(HAM) is used for analytic treatment of the telegraph equations .This method can provide analytical solutions to the problems by just utilizing the initial conditions. The proposed iterative scheme finds the solution without any discretization, linearization or restrictive assumptions.The proposed method solves nonlinear problems without using Adomain polynomials which is the advantage of this method over Adomain Decomposition method.The results reveal that the HAM is very effective, fast, simple, convenient, flexible and accurate. Outcomes prove that HAM is in very good agreement with ADM,VIM HPM.